SOCIAL REFORMS IN SOCIETY ARE AN IMPORTANT CRITERION FOR REALIZING THE IDEAS OF NATIONAL DEVELOPMENT - Alisher Qurbon o’g’li Ibragimov (American Journals Publishing, 2022)
In this article, the process of national growth in our country, its progress, reforms in the social and political sphere and its progress, the emergence of ideas of national development, pluralism and the provision of human interests, its importance in the growth of the country and society, the principles of national growth, human value and humanistic reforms are reflected.
Keywords: National growth, human, democracy, legal state, civil society, human interest, freedom, welfare, social values